The relationship of capital structure towards firm's performance: focusing on the technological sector / Zuraidah Ahmad ... [et al.] - Ahmad, Zuraidah; Mohamed Yousop, Nur Liyana; Ramdhan, Nur 'Asyiqin; Sipon, Zuraidah; A. Latif, Ruziah; Hassan, Suzana; Mohd Hasan Abdullah, Norhasniza; Ismail, Ummi Mariah (Universiti Teknologi MARA, Kedah, 2021)
Capital structure is an important decision towards firm financing when it comes to mixing debt and equity. In addition, capital is the primary resource for the firms. A good decision about the capital can provide maximized returns that ultimately give an impact on the firm's value and overall operations and growth. Hence, risks and other factors also must be deliberated in determining a good debt or equity financing. The main objective of this study is to investigate the relationship of long-term debt (LTD), shortterm debt (STD), tangibility (net fixed asset) and firm size (natural log total assets) towards firm performance which is measured by return on equity in technological sectors in Malaysia. The collection of data focuses on the period from 2012 to 2017 which is equivalent to six years. Eleven companies were selected as a sample that contributed to the 66 observations. Model Pool OLS, Random Effect and Fixed Effect were applied in order to investigate the relationship of firm performance in this industry. At the end of the study, LTD, STD and tangibility were found to be statistically insignificant while only firm size was statistically significant and had a positive relationship towards firm performance in the technological sector.